The STUDENTSCALE: Measuring Students’ Motivation, Interest, Learning Resources and Styles - Moreira, Rui (2015)
5th Global Innovation and Knowledge Academy Conference, GIKA 2015, Valencia, Spain, July 14-16, 2015, Proceedings